COMPREHENSIVE REVIEW OF THE EFFECTIVENESS OF NOVEL TREATMENTS IN RARE DISEASES - 1Hashem Ahmed A Kholedi, ‏2Emad Abdulhamid Aljohani, ‏3Hani Mabrouk Alsaedi, ‏4Mohammed Zakarya Qamrldin, 5‏Hanaa Abdullah Abduh Alyamani, ‏6Abdulrahman Ali Almasoud, ‏7Majed Ibrahim Muafa, 8Shatha Ismail Abdulwahab Younis (Chelonian Research Foundation, 2022)
The rare and frequently ineffective nature of rare diseases poses a significant challenge in determination and treatment. For a long time, there has been an increase in endeavours to create novel medications to meet the neglected therapeutic needs of influenced people. This survey gives a comprehensive study of the benefits of these novel treatments for an assortment of rare infections. This audit included a comprehensive writing audit and a cautious audit of the writing to assess the viability, security, and general effect of these mediations. Utilize charts, tables, and charts to clarify critical discoveries and progress understanding and knowledge into the clinical picture of rare illnesses. Through a comprehensive talk, this survey addresses the confinements of inquiry and clinical hone. It investigates future bearings, giving the premise for proposals for making strides in healthcare in this vital area. Keywords: rare diseases, novel treatments, Effectiveness, Efficacy, Safety, Literature review, Recommendations